Comparison of Drug Inventory Management in Public and Private Hospitals in Kendari City - Fitra Saripati, Wa Ode; Azizi Jayadipraja, Erwin; Umi Nurlila, Ratna (Waluya The International Science of Health Journal, 2025)
Introduction: Drug inventory management is an important aspect in supporting the effectiveness of health services in hospitals, especially in providing quality drug needs. There are differences in the characteristics of drug supply management between public and private hospitals. These differences include aspects of policy, resources, regulation, and procurement flexibility. This attracted researchers to conduct a study aimed at comparing drug supply management systems between public and private hospitals, especially in Kendari City. Method: The research used a qualitative approach with data triangulation through in-depth interviews, observations, and document studies. Informants consisted of heads of pharmacy installations, pharmacists, and hospital management representatives. Result: The results of in-depth interviews showed differences in drug procurement management between public and private hospitals. Public hospitals have a more structured system following formal regulations such as e-catalogue, while private hospitals are more flexible. The ABC method has also been applied in all hospitals in mapping drug classifications although the implementation differs in each hospital depending on the size of the budget, the competence of human resources, and the availability of supporting systems and data required. The EOQ method has not been optimally implemented due to limited data and information systems. A common problem faced by hospitals is drug stock-outs, which have an impact on patient satisfaction. Conclusion: The effectiveness of drug management in hospitals is generally considered to be good. There are differences and similarities in drug management between public and private hospitals. Stock out is a common problem in drug supply management in hospitals.